Fraksinasi Material Boulder Nikel Laterit PT Gag Nikel Daerah Pulau Gag Waigeo Barat Kepulauan, Raja Ampat, Papua Barat - Jarot, Jarot Pujiono (ReTII, 2022)
ABSTRACT The world’s nickel demand is increasing along with the rapid development of nickel smelters which are not matched by the supply on the London Metal Exchange (LME). In this regard, Indonesia as one of the nickel-producing countries which have nickel reserves of 72 million tons of Ni and is the owner of 52% of the world’s nickel reserves, continues to increase its production capacity. PT Antam, one of the state-owned companies under MIND ID, has an important role in the world’s nickel supply. PT Gag Nickel is a subsidiary of PT Antam Tbk located on Gag Island, which is producing high-grade nickel which supplies domestic nickel needs. Development continues at PT Gag Nickel to anticipate the surge in demand for high-grade nickel as well as an increase in production targets in 2022 and 2023. One of the nickel development initiatives at PT Gag Nickel is to test the potential nickel content (Ni) contained in boulders with grain size >20cm. This study is one method to utilize mining waste in the form of boulders measuring > 20 cm which is considered to have no economic value.